Microbial community diversity and function analysis of Aconitum carmichaelii Debeaux in rhizosphere soil of farmlands in Southwest China - Pu, Tingting; Liu, Jie; Dong, Jingjing; Qian, Jun; Zhou, Zhongyu; Xia, Conglong; Wei, Guangfei; Duan, Baozhong (Frontiers in Microbiology, 2022)
Understanding how microbial communities affect plant growth is crucial for sustainable productivity and ecological health. However, in contrast with the crop system, there is limited information on the microbial community associated with the medicinal plant. We observed that altitude was the most influential factor on the soil microbial community structures of Aconitum carmichaelii Debeaux. For community composition, bacterial reads were assigned to 48 phyla, with Proteobacteria, Acidobacteriota, and Actinobacteriota being the dominant phyla. The fungal reads were assigned to seven phyla, and Ascomycota was the predominant phylum detected in most groups. The four dominant phyla were categorized as keystone taxa in the co-occurrence networks, suggesting that they may be involved in soil disease suppression and nutrient mobility. Bacterial co-occurrence networks had fewer edges, lower average degree, and lower density at YL1, HQ1, HQ2, BC, and DL than fungal networks, creating less intricate rhizosphere network patterns. Furthermore, the bacterial and fungal communities showed strong distance decay of similarity across the sampling range. Overall, this study improves our understanding of regulating rhizosphere microbial communities in soil systems and also provides potential production strategies for planting A. carmichaelii.